INCLUSIVE EDUCATION AND AUTISM: : EXPERIENCES IN THE PUBLIC SCHOOL SYSTEM FROM THE PERSPECTIVE OF PSYCHOLOGY (PRÁXIS EM SAÚDE, 2026)
This study is an experience report carried out in a municipal public elementary school in the state of Maranhão. The objective is to describe and present the experiences of undergraduate Psychology students from the Federal University of Maranhão, highlighting the gap between the legal guarantees and rights of individuals with Autism Spectrum Disorder and the reality within the educational context. The experience was developed through a technical visit to the institution, including interviews and observation of the school community. The experience highlighted the importance of the school psychologist’s role in promoting school inclusion and mediating psychosocial issues. However, it was found that the absence of this professional limits the development of effective practices within the educational context.
Keywords: Autism Spectrum Disorder; School Inclusion; Challenges; School Psychology